Landau–Zener Topological Quantum State Transfer. Issue 3 (24th January 2019) - Longhi, Stefano; Giorgi, Gian Luca; Zambrini, Roberta
Abstract: Fast and robust quantum state transfer (QST) is a major requirement in quantum control and in scalable quantum information processing. Topological protection has emerged as a promising route for the realization of QST robust against sizable imperfections in the network. Here, a scheme is presented for robust QST of topologically protected edge states in a dimeric Su–Schrieffer–Heeger spin chain assisted by Landau–Zener tunneling. As compared to topological QST protocols based on Rabi flopping proposed in recent works, the method is more advantageous in terms of robustness against both diagonal and off‐diagonal disorder in the chain, without a substantial increase of the interaction time. Abstract : A topologically protected quantum state transfer protocol, based on Landau–Zener tunneling in a dimerized spin chain model, is theoretically proposed. The transfer method fully exploits the topological nature of the edge states in the network and shows enhanced robustness against structural disorder in the chain as compared to other protocols, such as those based on adiabatic Rabi flopping.